The gut microbiome as a major source of drug-resistant infections: emerging strategies to decolonize and target the gut reservoir - Sharma, Ishrya; Sudarsanan, Drishya; Moonah, Shannon (Frontiers in Cellular and Infection Microbiology, 2025)
Infections caused by antimicrobial-resistant bacteria represent a significant global health crisis that continues to worsen, creating an urgent need for alternative treatment and prevention strategies. A major source of drug-resistant bacteria is the human gut. The gut microbiota consists of bacteria that are frequently exposed to antibiotics, leading to selective pressure that promotes the development of resistant strains such as carbapenem-resistant Enterobacterales (CRE) and vancomycin-resistant enterococci (VRE). These drug-resistant bacteria can spread from the gut to other body sites, leading to hard-to-treat and potentially life-threatening infections such as bacteremia, surgical site infections, and urinary tract infections. Targeting the gut reservoir is essential in the fight against antimicrobial resistance. In this review, we focus on emerging non-antibiotic strategies aimed at eliminating drug resistant bacteria from the gut before they cause invasive infections, with particular emphasis on clinical evidence. Approaches discussed include fecal microbiota transplantation, bacteriophage therapy, antimicrobial peptides, probiotics, and dietary interventions. Optimizing these strategies, while continuing to explore newer approaches, will be essential to combat the growing threat of drug-resistant infections.